An evaluation of factors influencing residential segregation in selected areas of Bauchi Metropolis, Northern Nigeria - Kasim, Rozilah; Salihu Muhammad, Maryam; Martin, David (MCSER Publishing, 2015)
Residential segregation, the spatial separation of population sub-groups within a given geographical area, is a phenomenon which is prevalent in both developed and developing countries like Nigeria. Earlier in Northern Nigeria this phenomenon was characterised by residential separation along ethnic lines (which led to the emergence of non-indigene settlements known as the “Sabon Gari”) and in the present time residential segregation is also found along religious lines. This paper is aimed at examining the factors influencing residential segregation in selected areas of Bauchi metropolis in Northern Nigeria. The objectives of the research are to identify the pattern and the factors influencing residential segregation in the study area, and to evaluate the significance of the factors on residential segregation in the study area. 6 areas were sampled from study area and the research was conducted through questionnaire survey. The data collected was analysed using the Statistical Package for Social Sciences (SPSS v21). The research uncovered that the main factors influencing residential segregation in the study area are individual and aggregate socioeconomic characteristics, and individual preference/taste/choice of neighbourhood. And the research revealed that there is a significant relationship between these factors and residential segregation.